2016
DOI: 10.1302/0301-620x.98b5.34996
|View full text |Cite
|
Sign up to set email alerts
|

Fatal pulmonary embolism following elective total hip arthroplasty

Abstract: This study proposes that aspirin may be an appropriate thromboprophylaxis agent when used as part of a multi-modal regimen, suggesting current guidelines should be reviewed. Cite this article: Bone Joint J 2016;98-B:585-8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 35 publications
1
30
0
1
Order By: Relevance
“…The optimum duration for VTE prophylaxis remains controversial because the appropriate length of aspirin prophylaxis after TJA is not well studied. The studies included in this systematic review reported various durations of aspirin prophylaxis including 14 days [28,29,46,50], 21 days [52,58], 3 weeks [51], 1 month/4 weeks [11,34,35,37,40,44], 5 weeks [32], and 6 weeks [3,7,15,22,23,25,26,31,38,39,42,43,53,54]. We found no significant difference between incidence of PE or DVT and the different durations of aspirin treatment examined (<4 weeks, 4 weeks, and >4 weeks).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The optimum duration for VTE prophylaxis remains controversial because the appropriate length of aspirin prophylaxis after TJA is not well studied. The studies included in this systematic review reported various durations of aspirin prophylaxis including 14 days [28,29,46,50], 21 days [52,58], 3 weeks [51], 1 month/4 weeks [11,34,35,37,40,44], 5 weeks [32], and 6 weeks [3,7,15,22,23,25,26,31,38,39,42,43,53,54]. We found no significant difference between incidence of PE or DVT and the different durations of aspirin treatment examined (<4 weeks, 4 weeks, and >4 weeks).…”
Section: Discussionmentioning
confidence: 81%
“…However, the appropriate dose of aspirin remains controversial. The studies included in this systematic review reported the various daily doses of aspirin of 75 mg/d [25,26], 81 mg/d [27], 100 mg/ d [28e30], 150 mg/d [31], 160 mg/d [11,32], 300 mg/d [33], 325 mg/ d [34e36], 650 mg/d [3,5e7,11,15,22e24,37e45], 1000 mg/d [46], 1200 mg/d [24,47e51], and 1300 mg/d [52e59]. Low-dose aspirin has been shown to be as effective as higher doses of aspirin in patients with acute coronary syndrome [64] and transient ischemic attack or minor stroke [65].…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that the incidence of mortality after arthroplasty is lower in patients using aspirin than in those using warfarin, 9 , 14 , 20 LMWH, ximelagatran, fondaparinux, or rivaroxaban. 14 , 138 Hunt et al 139 showed that mechanical and chemical thromboprophylaxis with heparin with or without aspirin were associated with a decreased 90-day mortality in 409 096 patients undergoing primary THA. They also reported 140 that the 45-day mortality with aspirin after TKA was slightly lower than the mortality with heparin, although this did not reach statistical significance.…”
Section: Does Aspirin Have Any Unintended Beneficial Effects?mentioning
confidence: 99%
“…The latter is not surprising as myocardial infarction and not PE is the main cause of mortality following arthroplasty. 141 PE is responsible for between 11.7% and 17.1% of 90-day mortality, 138 , 141 , 142 while a myocardial infarction is responsible for 25.9%. 141 The true cause of death in many patients who do not have an autopsy remains unknown.…”
Section: Does Aspirin Have Any Unintended Beneficial Effects?mentioning
confidence: 99%
“…Recent changes in the guidelines of both the AAOS and the ACCP converge in favor of aspirin use in the context of a multimodal approach in correctly selected patients. Bayley et al [33], in a prospective study involving 7983 THAs, suggest aspirin as an appropriate thromboprophylactic agent as part of a multimodal regimen, noting that pulmonary embolism is rare in this context and that potent anticoagulants have a higher rate of complications.…”
Section: Discussionmentioning
confidence: 99%